A SHARK’S RAMPAGE REVEALING DARK SIDE OF NATURE IN GENS’S FILM UNDER PARIS: AN ECOGOTHIC ANALYSIS (Al-Aasar, 2025)
This research aims to explore nature’s wrath when it is suppressed and exploited by human anthropocentric behaviour, examining the themes of environmental issues and eco-horror in the movie Under Paris directed by Xavier Gens by focusing on the fact that nature is not a passive victim. By using Ecogothic lens, this article argues that the movie Under Paris critiques anthropocentric views where humans are considered the supreme and central creature of the universe, warning human race to stop exploiting nature in the name of modernism because nature’s retribution can be destructive. The idea of Dark Ecology introduced by Morton is employed in this study to explore film Under Paris alongside the concepts given by Noël Carroll and Linda Williams. Qualitative research method and close reading of script has been used to conduct the research, focusing also on visuals and scenes of the movie. The study aims to examine the factors contributing to nature’s exploitation as well as the disastrous consequences of this negligence. By conducting research on Under Paris, this study contributes to the contemporary debates about causes and consequences of ecological balance disruption, urging the global community to take serious actions to co-operate with nature and create a world where humans and nature can live in solidarity.